Cyclooxygenase inhibitor associated with carboplatin in treatment of metastatic nasal carcinoma in dog - Fonseca-Alves, Carlos Eduardo [UNESP]; Corrêa, Aline Gonçalves [UNESP]; Elias, Fabiana; Calazans, Sabryna Gouveia (Hindawi, 2014)
A 10-year-old, intact male, pinscher was presented with unilateral bloodstained nasal discharge, sneezing, dyspnea, zygomatic arch deformity, submandibular lymph node increase, blindness in right eye, and exophthalmia. After clinical examination, it was found that the animal presented with upper respiratory tract dyspnea origin, possibly caused by an obstructive process. Complete blood count (CBC), ocular ultrasonography, thoracic radiographs, mandibular lymph node, and nasal sinus fine needle aspiration were performed. The right mandibular lymph node excisional biopsy was conducted and a tumor sample was obtained through the nasal fistula at hard palate. The material was processed, paraffin embedded, sectioned, and stained with hematoxylin and eosin. Immunohistochemical staining for cytokeratin (AE1/AE3), vimentin, and COX-2 was performed. After histopathological evaluation nasal carcinoma diagnosis was obtained. Chemotherapy was established with carboplatin 300mg/m2 intravenously- four cycleswith intervals of 21 days-and firocoxib 5mg/kg orally every 24 hours for 7months.After 7months the treatment started, the animal presented with ataxia, vocalization, hyperesthesia, and anorexia. Due the clinical condition presented, the animal owner opted for performing euthanasia. The chemotherapy protocol was effective causing the disease stagnation, minimizing the clinical signs, and extending patient survival and quality of life.